2022
DOI: 10.1002/ana.26444
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Frontal Gamma Activity in Alzheimer Disease Patients

Abstract: Objective In Alzheimer disease (AD) animal models, synaptic dysfunction has recently been linked to a disorder of high‐frequency neuronal activity. In patients, a clear relation between AD and oscillatory activity remains elusive. Here, we attempt to shed light on this relation by using a novel approach combining transcranial magnetic stimulation and electroencephalography (TMS‐EEG) to probe oscillatory activity in specific hubs of the frontoparietal network in a sample of 60 mild‐to‐moderate AD patients. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 55 publications
6
26
0
Order By: Relevance
“…Table 1 and Figure 3 report the E–fields computed for the 12 conditions explored. Our results showed that, even with the lowest intensity of stimulation (100% RMT), the estimated E–fields were well above the threshold of 40 V/m to evoke a reliable TMS–evoked EEG response [ 22 , 26 ]. To note that the E–fields obtained at 0° and 90° CO were higher than those at 180° and 270°; this might, to an extent, have contributed to our results (see below).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 and Figure 3 report the E–fields computed for the 12 conditions explored. Our results showed that, even with the lowest intensity of stimulation (100% RMT), the estimated E–fields were well above the threshold of 40 V/m to evoke a reliable TMS–evoked EEG response [ 22 , 26 ]. To note that the E–fields obtained at 0° and 90° CO were higher than those at 180° and 270°; this might, to an extent, have contributed to our results (see below).…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that the chosen stimulation intensities could generate an electric field (E–field) in the cortex sufficient for a reliable TEP, i.e., at least 40 V/m [ 22 , 26 ], we computed the induced E–field over the TMS target with SimNIBS v3.2, an open–source simulation package that integrates segmentation of MRI scans, mesh generation and FEM E–field estimate [ 27 ]. The E–field was computed for the twelve stimulation conditions resulting from the combination of four COs (0°, 90°, 180°, 360°) and three SIs (100%, 120%, 140% RMT).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in AD animal models, the synaptic dysfunction has been linked to a disorder of high-frequency neuronal oscillatory activity, in particular in the gamma range (40 Hz) [ 19 , 20 ]. Accordingly, in a recent work, TMS combined with EEG (TMS-EEG) recordings have shown that AD patients had more prominent decrease in gamma activity in the prefrontal cortex with a stronger impairment of LTP-like plasticity mechanisms and more prominent cognitive decline [ 21 ]. Interestingly, the optogenetic entrainment of fast-spiking parvalbumin-positive interneurons of AD animal model at gamma frequencies was able to reduce the total amyloid levels, probably acting on both neurons and microglia [ 22 ].…”
Section: Introductionmentioning
confidence: 99%